Improving the Start in Swimmers with the Help of Plyometric Exercises - C. Tartaleanu; D. Ortanescu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
Physical preparation is one of the most important factors of sports training in achieving great performance. In this material, the problem of developing the skills of swimmers to improve their start with the help of plyometric exercises as well as strength circuits is studied. The experiment was carried out with performance athletes, 13-14 years old. The methodical ways related to the volume and content of the use of exercises on land and in water were established by using modern technical means of preparation, the developed method proving effective and can be applied in the training process.